Proposing an Affordable Plasma Device for Polymer Surface Modification and Microbial Inactivation - Chiappim, William [UNESP]; Kodaira, Felipe Vicente de Paula [UNESP]; Castro, Gisele Fátima Soares de [UNESP]; Silva, Diego Morais da [UNESP]; Tavares, Thayna Fernandes [UNESP]; Almeida, Ana Carla de Paula Leite [UNESP]; Leal, Bruno Henrique Silva [UNESP]; Quade, Antje; Koga-Ito, Cristiane Yumi [UNESP]; Kostov, Konstantin Georgiev [UNESP] (MDPI, 2024)
This study proposes an affordable plasma device that utilizes a parallel-plate dielectric barrier discharge geometry with a metallic mesh electrode, featuring a straightforward 3D-printed design. Powered by a high-voltage supply adapted from a cosmetic plasma device, it operates on atmospheric air, eliminating the need for gas flux. Surface modification of polyethylene treated with this device was characterized and showed that the elemental composition after 15 min of plasma treatment decreased the amount of C to ~80 at% due to the insertion of O (~15 at%). Tested against Candida albicans and Staphylococcus aureus, the device achieved a reduction of over 99% in microbial load with exposure times ranging from 1 to 10 min. Simultaneously, the Vero cell viability remained consistently high, namely between 91% and 96% across exposure times. These results highlight this device’s potential for the surface modification of materials and various infection-related applications, boasting affordability and facilitating effective antimicrobial interventions.
Keywords: affordable cost; antimicrobial effects; Candida albicans; cold atmospheric plasma; cytotoxicity; dielectric barrier discharge; polyethylene; polymer surface modification; Staphylococcus aureus; Vero cell